In Vitro Antimicrobial Activity of Javanese Tamarind Leaves Infusion (Tamarindus indica Linn.) in Escherichia coli - Suryadi, Caroline; Rusmana, Djaja; Evacuasiany, Endang (Maranatha Christian University, 2015)
Escherichia coli is the most common bacteria that cause diarrhea. Based on Kurniawatiâs research, ethanol extract of tamarind leaves has an antimicrobial effect to Escherichia coli. This study aims to determine the antimicrobial effect using disk diffusion method, the minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) of tamarind leaves infusion against Escherichia coli.Â This research was done using a real laboratory experimental design with tamarind leaves infusion and Escherichia coli microbes as the research objects. Zones of inhibition were observed using disk diffusion method by putting the tamarind leaves infusion disks on Mueller-Hinton agars with Ampicillin antibiotic for comparison, followed by observing the MIC using macro broth dilution methodÂ and MBC. The result of disk diffusion showed that tamarind leaves infusion had no zone of inhibition, whereas the mean value of the zones of inhibition of ampicillin is 17.2 mm. The MIC of tamarind leaves infusion is 62.5 mg/mL. Average growth of bacteria Â for the MBC of tamarind leaves infusion at 125 mg/mL and 62.5 mg/mL concentration are 13 CFU/mL and >300 CFU/mL. It can be concluded that tamarind leaves infusion has antimicrobial activity effect against E.coli and that effect is bacteriostatic.Â Keywords: Tamarindus indica Linn, Escherichia coli, MIC, MBC